Drug delivery therapies I: general trends and its importance on bone tissue engineering applications - Malafaya, P. B. (2002)
[Excerpt] Drug delivery systems are not a new subject in the Biomaterials/Biomedical field. However, they are almost in continuous fashion since the 1940s, when the first drug delivery system was developed with the aim of raising drug concentration in the blood [1], thus decreasing the periodicity of the drug uptake by the patient. The increasing need for the improvement of health care has been the driving force for the growth of this field of research that became a powerful tool in health care. The concept of drug delivery systems is continuously mutating, although in the ultimate case these systems intend to achieve either a spatial and/or a temporal control of the bioactive agent delivery. The definition of drug delivery system can be of a system that is capable of releasing a carried bioactive agent in a specific location at a specific rate. The main aim of this type of system is to facilitate the dosage and duration of the drug effect, causing the minimal harm to the patient and improving human health [2], since they allow for the reduction of the dosage frequency [3]. Most drug delivery systems currently applied in patients are capable of rate and/or time controlled release. The potential therapeutic advantages of these systems [4] appear to be several fold, such as the in vivo predictability of the release rate, minimised peak plasma levels, and thereby, reduced risk of adverse reactions, extended duration of action and reduced inconvenience of frequent re-dosing thus improving the patient compliance. [...]